1987
DOI: 10.1038/330489a0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-termination of transcription within the long terminal repeat of HIV-1 by tat gene product

Abstract: Human immunodeficiency virus-1 (HIV-1) gene expression is controlled by cellular transcription factors and by virally encoded trans-activation proteins of the HIV-1 tat and art/trs genes, which are essential for viral replication. Tat trans-activates HIV-1 gene expression by interacting with the trans-acting response element (TAR) located within the HIV-1 long terminal repeat (LTR) (ref. 2). In transient expression assays, tat mediates its effects largely by increasing the steady-state levels of messenger RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
713
3
8

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 867 publications
(764 citation statements)
references
References 0 publications
34
713
3
8
Order By: Relevance
“…One could therefore explain part of the synergism in transcriptional activation if interaction of acidic activators with TFIIH stimulates melting of the DNA at the promoter. This phenomenon would have been difficult to detect in vitro because acidic activators also stimulate formation of the closed preinitiation complex (65,112,114 18) and increasing the processivity of chain elongation by RNA polymerase 11 (52,54,61,71). Similarly, other typical activators, including VP16, may also generally stimulate chain elongation by RNA polymerase 11 (119).…”
Section: Discussionmentioning
confidence: 99%
“…One could therefore explain part of the synergism in transcriptional activation if interaction of acidic activators with TFIIH stimulates melting of the DNA at the promoter. This phenomenon would have been difficult to detect in vitro because acidic activators also stimulate formation of the closed preinitiation complex (65,112,114 18) and increasing the processivity of chain elongation by RNA polymerase 11 (52,54,61,71). Similarly, other typical activators, including VP16, may also generally stimulate chain elongation by RNA polymerase 11 (119).…”
Section: Discussionmentioning
confidence: 99%
“…A U-rich bulge located just below the loop is important for TAT recognition. It has been suggested that TAT may regulate both transcriptional initiation and elongation with Kao et al (1987) being the first to demonstrate that it activates HIV transcription by behaving as an antiterminator like protein. By analyzing the expression of an HIV LTR-driven CAT gene in transient expression assays, it was shown that transcripts did not elongate past the viral TAR region in the absence of a cotransfected TAT gene; this was indicated both by runoff transcription analysis and by the detection of truncated RNAs in the cytoplasm.…”
Section: Regulation Of Transcriptional Elongation In Hiv Expressionmentioning
confidence: 99%
“…In the absence of Tat, RNA polymerase II (pol II) terminates transcription of the HIV genome prematurely, resulting in primarily short transcripts. Interactions between Tat and TAR convert pol II into its processive form and lead to the efficient production of full-length viral transcripts (15,24,27,32,37).…”
mentioning
confidence: 99%
“…Following phenol-chloroform extraction, the transcripts were precipitated with ethanol and separated on a 5% denaturing polyacrylamide gel. Wild-type (LTR) and mutated (U23A) HIV-1 promoter constructions yielded specific HIV-1 runoff transcripts of 750 and 620 nt, respectively (24,48). Recombinant Tat (100 ng) was expressed in E. coli and bound to streptavidin-agarose beads as described above.…”
mentioning
confidence: 99%